2022
DOI: 10.3389/fmicb.2022.922089
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Biosynthesis, and Biological Activity of Polycyclic Xanthones From Actinomycetes

Abstract: Natural products from actinomycetes serve as a crucial source of clinical pharmaceuticals, especially antibiotics and anticancer agents. Among them, polycyclic xanthones belong to a growing group of highly oxygenated aromatic polyketides with a xanthone-containing angular hexacyclic framework. These biosynthetically unique small molecules are of great interest due to their wide spectrum of biological activities, especially the remarkable antibacterial activity against gram-positive bacteria and the significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Figure 5 shows examples of type II PKS products that first cyclize into linear or angular carbocycles, but then subsequently rearrange after this process to form heterocycles with an enormously diverse level of functionality. The calixanthomycins and other xanthones are predicted to derive from a tridecaketide [99,105]. Oxidation and Baeyer-Villiger rearrangement is hypothesized to create an epoxy ester that hydrolyzes, epoxide opens, and subsequently decarboxylates to form the xanthone core and reestablish aromaticity [106].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows examples of type II PKS products that first cyclize into linear or angular carbocycles, but then subsequently rearrange after this process to form heterocycles with an enormously diverse level of functionality. The calixanthomycins and other xanthones are predicted to derive from a tridecaketide [99,105]. Oxidation and Baeyer-Villiger rearrangement is hypothesized to create an epoxy ester that hydrolyzes, epoxide opens, and subsequently decarboxylates to form the xanthone core and reestablish aromaticity [106].…”
Section: Figurementioning
confidence: 99%
“…Derivatives of chartreusin have already been the subject of some biosynthetic pathway engineering [132]. Like chartreusin, jadomycins [133], such as jadomycin B [134], are ring-opened and decarboxylated The calixanthomycins and other xanthones are predicted to derive from a tridecaketide [99,105]. Oxidation and Baeyer-Villiger rearrangement is hypothesized to create an epoxy ester that hydrolyzes, epoxide opens, and subsequently decarboxylates to form the xanthone core and reestablish aromaticity [106].…”
Section: Figurementioning
confidence: 99%
“…Polycyclic xanthones are aromatic polyketide derivatives assembled from type II PKSs using malonyl-CoA as the substrate, and they have an angular hexacyclic framework that is highly oxygenated and contains a xanthone substructure and an isoquinolone or isochromane moiety [63]. The structural diversity of polycyclic xanthones depends on the variation in the oxidation state of the xanthone moiety and the diversity of substituents, including hydroxyl, halogen atoms, and sugar moieties [64]. The variation of the oxidation state of the quinone/hydroquinone in the isoquinolone moiety and the diversity of substituents, including alkyl, hydroxyl, and halogen atoms, also contribute to the structural diversity of polycyclic xanthones [64].…”
Section: Xanthone Polyketidesmentioning
confidence: 99%
“…The structural diversity of polycyclic xanthones depends on the variation in the oxidation state of the xanthone moiety and the diversity of substituents, including hydroxyl, halogen atoms, and sugar moieties [64]. The variation of the oxidation state of the quinone/hydroquinone in the isoquinolone moiety and the diversity of substituents, including alkyl, hydroxyl, and halogen atoms, also contribute to the structural diversity of polycyclic xanthones [64]. The methylene dioxybridge or the oxazolidine ring fused with the angular hexacyclic framework is also essential for the structural diversity of xanthones [64].…”
Section: Xanthone Polyketidesmentioning
confidence: 99%
“…Some general reviews on xanthones can be found in the recent literature; however, only a few mentioned limited types of BPXNPs, 2,9–12 and no systematic collections and classifications have been performed to date. In this review, we systematically summarize the bacterial-originating BPXNPs, exploring their structural diversities and various biological activities and introducing the pharmacological interest in their cytotoxic and antitumor activities through related structure–activity research.…”
Section: Introductionmentioning
confidence: 99%